Sage 50 training - Endogan, Vicki; Safari eBooks ([S.l.] : InfiniteSkills, 2010)
"This Sage 50 Training video breaks mastering this powerful accounts package down into easy-to-follow stages. The lessons are practical and use a fictitious company as a base to teach the fundamentals of bookkeeping. The format of the lessons is aimed towards both users who are new to Sage accounting or are upgrading from prior versions.Author Vicky Endogan starts at the very foundations of company bookkeeping and shows how to correctly setup Sage, after which she looks at each process in great detail, highlighting the common pitfalls that newcomers to Sage often make. The visual nature of the training makes learning easy, even the most complex of topics are broken down into simple to follow stages. Users can watch the lessons in sequential order or jump to topics of specific interest. By the conclusion of this Sage training video, users will have an in-depth knowledge of good bookkeeping practices and a solid understanding of using Sage in a commercial environment." --Resource description page.
Title from resource description page (viewed July 28, 2011).
Presenter, Vicki Endogan.
Keywords: Small business -- Accounting -- Data processing; Electronic books